Effect of Nitrate Levels on Nitrogen Accumulation, Seed Yield and Quality of Soybean Cultivars - Myint Myint Maw,; Sutkhet Nakasathien,; Ed Sarobol, (Agriculture and Natural Resources, 2011)
Soybeans (Glycine max [L.] Merr.) were grown in nutrient culture containing various concentrations of NO3- in the forms of KNO3 and Ca(NO3)2. The objective was to evaluate the seed yield and quality responses of soybean cultivars to NO3- solution. The experiment was conducted in a hydroponic solution using a split plot in randomized complete blocks with three replications in the greenhouse at the Department of Agronomy, Faculty of Agriculture, Kasetsart University, Bangkok, Thailand. Three levels of NO3- (5, 10, 15 mM) formed the main plots and three soybean cultivars (CKB1, SJ5, CM60) were the sub-plots. Nitrate application increased the yield of soybean cultivars and this increase was mainly associated with dry matter accumulation in leaves at R5. In comparison with the control (5 mM), the highest NO3- level (15 mM) resulted in higher leaf N accumulation at the R5 stage by an average of 82, 37 and 32% for SJ5, CKB1 and CM60, respectively. The maximum seed yield (41.43 g plant-1) produced by the SJ5 cultivar under the highest NO3- level seemed to be supported by the significantly largest value of whole plant biomass and nitrogen content (%) in leaves at the R5 stage.